PERAN FORUM PEDULI AIR SUSU IBU DALAM MENDUKUNG PEMBERIAN AIR SUSU IBU EKSKLUSIF DI KOTA MATARAM PROVINSI NUSA TENGGARA BARAT - , Yuni Widiastuti; , dr. Mubasysyir Hasanbasri, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : The World Health Organization (WHO) has recommended exclusive breastfeeding in infants aged 0-6 months. Exclusive breastfeeding during the first 6 months of life children are the strategies needed to improve the survival chances of children. Although the practice has been widespread breastfeeding among mothers in the whole world but exclusive breastfeeding for 6 months is still very low. It is caused by variety of factors which are sociodemographic determinants of nursing, psychosocial, health care, biomedical constraints, attributes society and public policy. A Very complex problem can not be solved by governments alone but require the participation of the whole society. The Indonesian government has issued the latest legislation on exclusive breastfeeding is the Indonesian Government regulation No 33 of 2012, which also included the importance of community support individuals, groups and organizations to support exclusive breastfeeding. Several studies have shown the role of the community can increase exclusive breastfeeding. Forum Peduli ASI is one form of local voluntary organizations that have committed to support exclusive breastfeeding. Objective: This study aimed to determine the role of the Forum Peduli ASI (local voluntary organizations) in supporting exclusive breastfeeding in Mataram. Results: The role of Forum Peduli ASI in support exclusive breastfeeding in Mataram is advocating the issuance of regulations on exclusive breasfeeding, educate and motivate the public and health workers, making the model successful mothers exclusively breasfeed and formula free area, as well as facilitating the preparation of materials communication, information, and education and the establishment of the Kelompok Pendukung ASI (KPA). Conclusion: Forum Peduli ASI turns voluntary organizations that are very strategic to strengthen the health system in the region.